IJHRM after 30 years: taking stock in times of COVID-19 and looking towards the future of HR research - Cooke, Fang Lee; Dickmann, Michael; Parry, Emma (Taylor & Francis, 2020)
In this paper, we take stock of what The International Journal of Human Resource Management (IJHRM) has achieved in the past 30 years since its inception in 1990. By analyzing the publication trends indicated by keywords, we find that research published in IJHRM has shifted from a collective focus with institutional implications towards more individual concerns with organizational implications with relevance to HRM practices. We present research theme and approaches that distinguish IJHRM from other HRM journals, and offer suggestions of what we see as some of the important issues for future research that will take us beyond the current trajectory of HRM studies.
Keywords: technology; uncertainty; future of work; global mobility; COVID-19; employee well-being